Assessing the factors of economic and environmental inefficiency of sunflower production in Pakistan: an epsilon-based measure model - Abbas, Adnan; Mushtaq, Zulqarnain; Ikram, Amir; Yousaf, Khurram; Zhao, Chengyi (Frontiers in Environmental Science, 2023)
Considering the growing pressure of the edible oil imports bill on Pakistan’s national accounts, the significance of sunflower cultivation is gaining more attention to meet the domestic edible oil demand. Given the declining area for sunflower production, this study explored the factors of economic and environmental inefficiencies affecting sunflower growers in Pakistan. The study adopted the epsilon-based measure (EBM) model at the first stage and the Tobit truncated regression model at the second stage to precisely estimate the economic and environmental inefficiencies in the data collected from 240 sunflower growers. Results found that out of 240, 69.9% of the sunflower growers are economically inefficient, while the average environmental inefficiency of sunflower growers is 56.3%. The findings further revealed that farmers’ age, cultivated land, and market distance are the driving factors of farmers’ economic and environmental inefficiencies. However, formal education, farming experience, and access to agricultural extension services decreased the farmer’s inefficiencies. Based on the present study’s findings, diverse policy options are presented to address the problem of contraction of the area under sunflower production.